DEVELOPMENT OF INSTRUCTIONAL MATERIALS TO IMPROVE SKILLS IN OPERATING INTEGERS USING THE ARTICULATE STORYLINE APPLICATION - Arizal, Arizal; Suratman, Dede; Yundari, Yundari; Rif'at, Mohammad; Hamdani, Hamdani (Universitas Tanjungpura, 2025)
This study was conducted to address the low level of students' skills in performing operations with integers. This issue arose because, since the Covid-19 pandemic, many elementary school students have experienced learning loss, which has impacted their learning processes upon entering secondary school. Therefore, to optimize classroom learning time, students were also provided with opportunities for independent learning using interactive instructional materials. This study employed a quantitative development method using the ADDIE model and involved 50 seventh-grade students from SMPN 1 Lembah Bawang and SMPN 3 Lembah Bawang. Data collection techniques included tests and interviews using questionnaires. The collected data were analyzed by comparing pre-test and post-test results, as well as calculating effect size to determine the extent of influence after using the instructional materials. The study resulted in the development of instructional materials validated by experts and shown to improve students' skills in integer operations. After using the developed materials, more than 50% of students demonstrated high proficiency in operating integers, compared to 66% who had low proficiency beforehand. The resulting effect sizes after using the instructional materials were categorized as medium (d = 0.7) and high (d = 1.0). It can thus be concluded that the developed instructional materials effectively enhance students